AN ANALYSIS VALUES OF CHARACTER EDUCATION IN UPIN AND IPIN FILMS ANIMATION AT KISAH RAJA PEMBURU EPISODE - Piqih Anggraini; Zariul Antosa (Yayasan Thaifah Manshurah Pekanbaru, 2022)
This study aims to describe the values of character building based on the application of character Education (PPK) in Upin and Ipin animation film at Kisah Raja Pemburu episode. It researched at Riau Universitty, Education Faculty which located on Kampus Bina Widya street Simpang Baru, Pekanbaru. This research design with a descriptive qualitative research. The basic technique used in this method teknik simak libat cakap. The object is the dialogs and the acts in Upin and Ipin animation film which contain and show the values of character building. The result of this study show four values which relies on Upin dan Ipin animation film at Kisah Raja Pemburu. It is: 1) Nasionalism, 2) Independent, 3) integrity, 4) Mutual assistance. Based on that values, mutual assistance is considered as the dominant character that lead the four character in mention. Then also in the Upin and Ipin research it shows that the characters are good to observed